Systematic Review of the Anti-Cancer Activity of Green Tea (Camellia sinensis)-Derived Compounds in Breast Cancer In Vitro - Susilo, Felicia Edgina; Surjaputra, Ilsa Valentina; Boentoro, Silvia Apriliani; Ariela, Yovita; Sulistyo, Bobby Prabowo (Indonesia International Institute for Life Sciences, 2021)
Breast cancer is the most common type of cancer occurring in women with increasing prevalence in these past few years. Although many targeted therapies have been developed to increase the specificity of the treatment, many patients still suffer from cancer resistance and relapse. Green tea, a common beverage derived from natural plants, has been shown to induce chemopreventive effects and exhibit anti-cancer activity through its catechins and polyphenols content. The main well-known compound that induces these effects is epigallocatechin-3-gallate (EGCG). Green tea also contains other naturally occurring compounds such as catechin (C), epicatechin (EC), epigallocatechin (EGC), epicatechin-3-gallate (ECG), and others. In this study, we assessed and compared the anti-cancer activity of these green tea-derived compounds towards different types of breast cancer cell lines. A total of 15 original research papers from PubMed, Google Scholar, and DOAJ databases were collected and evaluated for the data extraction. The results showed that EGCG was the most potent compound in green tea that was able to reduce cell viability, wound closure, and induce apoptosis even in highly aggressive MDA-MB-231 and lower grade MCF-7 cell lines with ranging concentration. The second potent compound was ECG, followed by EGC and EC that exhibited intermediate effects. Lastly, catechin was shown to have the lowest anti-cancer activity among all other compounds. Flavonols were also shown to exert cytotoxic effects toward breast cancer cells. Moreover, further study is needed to discover the exact mechanism of each compound and determine its relationship toward different types of breast cancer cell lines.